The influence of organizational culture, transformational leadership on organizational citizenship behaviors, and organizational commitment through employee engagement - Hidayat, Cecep; Hermawan, Asep; Berliyanti, Dita Oki (Indonesian Journal of Education and Social Sciences, 2024)
This study evaluates the impact of Organizational Culture and Transformational Leadership on Organizational Commitment and Organizational Citizenship Behavior through Employee Engagement in non-formal educational institutions (PKBM) in West Java. Data from 291 respondents were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. Results show that Organizational Culture and Transformational Leadership significantly influence Employee Engagement. Organizational Culture and Employee Engagement affect Organizational Citizenship Behavior, while Employee Engagement influences Organizational Commitment. Employee Engagement serves as a mediator between Organizational Culture and Transformational Leadership and Organizational Commitment and Organizational Citizenship Behavior. However, Organizational Culture and Transformational Leadership do not directly impact Organizational Commitment, and Transformational Leadership does not significantly influence Organizational Citizenship Behavior. Practical implications suggest enhancing institutional performance for the well-being of educators. The study contributes to the Integrative Organizational Behaviors Model, rooted in Social Exchange Theory, providing insights for future research on Organizational Behavior.